Treatment of Hemophilia A with a Highly Purified Factor VIII Concentrate Prepared by Anti-FVIIIc Immunoaffinity Chromatography - Addiego, Joseph E, Jr.; Gomperts, Edward; Shu-Len, Liu; Bailey, Patricia; Courter, Suzanne G; Lee, Martin L; Neslund, Gerald G; Kingdon, Henry S; Griffith, Michael J (Thrombosis and Haemostasis, 1992)
To reduce the risk of pathogenic virus transmission associated with the therapeutic administration of plasma-derived antihemophilic factor (FVIIIc), a process utilizing anti-FVIIIc immunoaffinity chromatography to isolate FVIIIc has been developed. In addition, the starting cryoprecipitate solution has been treated with an organic solvent/detergent mixture to inactivate lipid-enveloped viruses. A final ion exchange chromatography step is used to further remove contaminants, e.g., anti-FVIIIc antibody, potentially leached with FVIIIc during the immunoaffinity step. The purified FVTII is stabilized for lyophili-zation and storage by the addition of human albumin. The monoclonal anti-FVIIIc antibody used in the immunoaffinity step of the process is not detectable in the final preparation. Viral reduction studies performed at specific steps of the process demonstrate that 11 logs of human immunodeficiency virus (HIV) and greater than 4-5 logs of other lipid-enveloped viruses are inactivated within the first 30 s of exposure to the solvent/ detergent mixture and 4-5 logs of various model viruses, e. g. Endomyocarditis virus (EMC), are physically removed during washing of the immunoaffinity column. The lyophilized product is reconstituted using sterile water in a matter of seconds.The pharmacokinetics of Hemofil® M were compared to those obtained using a standard heat-treated concentrate (Hemofil® CT) in five severe factor VIII deficient hemophiliacs in a randomized, cross-over study. No statistically significant differences were observed in mean half life (p >0.6) or median recovery (p = 0.4) between the two preparations. No clinically significant adverse effects were observed in patients receiving either FVIII preparation.In addition, 43 patients at 18 different centers underwent pharmacokinetic studies, with a nominal dose of 50 u/kg FVIIIc Hemofil® M. The mean recovery was 103.6%, and the t1/2 was 14.6 h. The recovery of FVIII in this group was as expected, providing an increase of assayed FVIII of approximately 2% per unit of FVTII/kg infused.Clinical trials using Hemofil® M have been initiated in 124 hemophilia A patients. The safety and efficacy of Hemofil® M has been established. To date, 0 of 60 patients tested have seroconverted to HIV. None of the previously untreated patients show clinical or laboratory evidence of Non-A, Non-B hepatitis (NANB), with 21 patients remaining negative as far as presence of antibodies to the Hepatitis C virus (a-HCV negative) at least 6 months after the initial infusion. There is no evidence of neoantigenicity, evidenced by seroconversion to murine antibody. An 8.7% (2 of 23) prevalence of anti-FVIIIc inhibitor development has been observed in previously untreated patients with FVIIIc⩽3%, receiving only the monoclonally purified solvent/ detergent treated FVIII concentrate while on study and on poststudy surveillance. All patients demonstrated clinical hemostasis following product use for either on demand bleeding or surgical prophylaxis.